DESIGN, OPTIMIZATION AND EVALUATION OF ACECLOFENAC FAST DISSOLVING TABLETS EMPLOYING STARCH VALERATE–A NOVEL SUPERDISINTEGRANT - SANTOSH KUMAR, R.; KANDUKURI, SHAMBHAVI; RAMYA, M.; LATHA, B. KUSUMA (International Journal of Applied Pharmaceutics, 2021)
Objective: To synthesize, characterize and evaluate starch valerate as a superdisintegrant in the formulation of aceclofenac fast dissolving tablets by employing 23 factorial design. Methods: Starch valerate was synthesized and its physical and micromeritic properties were performed to evaluate it. The fast dissolving tablet of aceclofenac was prepared by employing starch valerate as a superdisintegrant in different proportions in each case by direct compression method using 23 factorial design for evaluation of tablet parameters like disintegration and dissolution efficiency in 5 min. Results: The starch valerate prepared was found to be fine, amorphous and free flowing. Starch valerate exhibited good swelling in water with swelling index (125.2%). The study of starch valerate was shown by fourier transform infrared spectra (FTIR). The drug content (200±5%), hardness (3.5–4 kg/sq. cm), and friability (<0.15%) has been effective with regard to all the formulated fast dissolving tablets employing starch valerate. The disintegration time of all the formulated tablets was found to be in the range of 14±0.04 to 25.7±0.02 sec. The optimized formulation F4 had the least disintegration time i.e., 12.8±0.02 sec. The wetting time of the tablets was found to be in the range of 76±0.21 to 217±0.17s. The In vitro wetting time was less (i.e., 28±0.02s) in optimized formulation F4. The water absorption ratio of the formulated tablets was found to be in the range of 46±0.12 to 100±0.27%. The percent drug dissolved in the optimized formulation F8 was found to be 99.93% in 5 min. Conclusion: Starch valerate, when combined with sodium starch glycolate, croscarmellose sodium, with aceclofenac, was found to be an effective super disintegrant which improved the dissolution efficiency and could therefore be used in the formulation of quick dissolving tablets to provide immediate release of the contained drug within 5 min.